Development Trends of Russian Federalism as a Basic State Administration Principle - Arina N. Benedisyuk (Вестник Кемеровского государственного университета. Серия: гуманитарные и общественные науки)
The boundaries of the public administration system tend to blur as a result of poor systematic approach of the legislator to this institution. The doctrine of the public administration system of the modern Russian state needs a profound rethinking to obtain a clear system of interacting state bodies. This article describes the development of Russian federalism as a basic, system-forming principle of the organization and functioning of the public administration system. The research revealed a number of legal gaps and contradictions. The analysis included important constitutional changes in the federal structure and its new subjects, the status of the State Council, the tendency to subfederal and municipal territorial enlargement, and the normative legal regulation of the status of federal districts. The author believes that a federal okrug is a fake territorial unit. New legislative provisions are needed to eliminate organizational complexions and non-systemic solutions.